Implementasi Kurikulum Merdeka Dalam Capaian Pembelajaran PAI Kelas X SMAN 1 Lembah Gumanti - Rizki, Riza Aulia; Ilmi, Darul (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This research aims to determine the implementation of the independent curriculum in PAI learning in class The type of research used is descriptive qualitative. The technique for collecting data in this research uses observation and interviews with data analysis through reduction, presentation and conclusion techniques. The results of the research obtained are the problems of the independent curriculum in PAI learning at SMAN 1 Lembah Gumanti, namely that many students have no interest in studying, to overcome this, educators use various methods or various models to attract students’ interest again, there are also students who If you have problems while learning, one way to solve these problems is through differentiated learning. Educator’s constraints in learning achievements of PAI elements (Al-Quran Hadith) in class because if students are not interested and teachers are unable to attract students, then learning outcomes will not be achieved.